2002
DOI: 10.4049/jimmunol.168.12.6486
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Functional Defects of Thymic and Epidermal Vγ3 Cells in IL-15-Deficient and IFN Regulatory Factor-1-Deficient Mice

Abstract: In this study, the role of IL-15 and its regulation by the transcription factor IFN regulatory factor-1 (IRF-1) in murine Vγ3 T cell development and activity is assessed. Compared with wild-type (WT) mice, reduced numbers of mature Vγ3 cells were found in the fetal thymus of IL-15−/− mice, while IRF-1−/− mice displayed normal frequencies. Vγ3+ dendritic epidermal T cells (DETCs) were absent in IL-15−/− mice but present in IRF-1−/− mice. DETCs from IRF-1−/− mice displayed morphologically a less mature phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 63 publications
4
74
0
Order By: Relevance
“…It has been shown that IL-15 plays a critical role in the development of TCR␥␦ i-IEL and TCR␥␦ s-IEL (9,12). Consistent with previous studies, TCR␥␦ skin IEL almost completely vanished in IL-15 KO mice and TCR␥␦ i-IEL were selectively reduced in IL-15 KO mice (Fig.…”
Section: Enforced Expression Of Bcl-2 Partially Restores the Numbers supporting
confidence: 80%
“…It has been shown that IL-15 plays a critical role in the development of TCR␥␦ i-IEL and TCR␥␦ s-IEL (9,12). Consistent with previous studies, TCR␥␦ skin IEL almost completely vanished in IL-15 KO mice and TCR␥␦ i-IEL were selectively reduced in IL-15 KO mice (Fig.…”
Section: Enforced Expression Of Bcl-2 Partially Restores the Numbers supporting
confidence: 80%
“…IL-7 is essential for rearrangement of the TCR␥ gene during ␥␦ T cell development (22,23) and may also increase ␥␦ T cell life span in the periphery (24). Although IL-15 is not required for ␥␦ T cell development in general, IL-15 Ϫ/Ϫ mice lack V␥5 ϩ epidermal ␥␦ T cells (25) and Thy1 Ϫ splenic and intestinal intraepithelial ␥␦ T cells (16,26).…”
Section: Cd4 T Cells ͉ Cd8 T Cells ͉ Homeostatic Proliferationmentioning
confidence: 99%
“…In regard to IL-15, studies indicated reductions in ␥␦ T cell subsets in IL-15 Ϫ/Ϫ , IL-15R␣ Ϫ/Ϫ , and IL-15R␤ Ϫ/Ϫ mice (26,47,48). It was also shown that lack of V␥3 ϩ dendritic epidermal T cells in IL-15 Ϫ/Ϫ mice could not be corrected by adoptive transfer of wild-type thymocytes (27), and that a V␥3 ϩ transgenic TCR could restore this cell subset in IL-7R␣ Ϫ/Ϫ mice, but not in IL-15R␤ Ϫ/Ϫ mice (45), further suggesting that IL-15 signals are redundant for ␥␦ T cell maturation, but required for localization in the skin. More recent studies using mixed bone marrow-chimera indicated that development of intraepithelial ␥␦ T cells requires IL-15R␤ expression by bone marrow-derived cells, and IL-15 and IL-15R␣ expression by parenchymal cells, consistent with a model in which IL-15 is transpresented by IL-15R␣-expressing cells to IL-15R␤/␥ c -expressing cells (28).…”
Section: Discussionmentioning
confidence: 97%
“…Both IL-7 and IL-15 are known to play significant roles in ␥␦ T cell development and/or tissue localization (22)(23)(24)(25)(26)(27)(28), but their effect on the overall ␥␦ T cell homeostasis has not been studied. Like conventional ␣␤ T cells, most ␥␦ T cells in LN and spleen expressed significant levels of the IL-7R␣ chain CD127 (Fig.…”
Section: ␥␦ T Cells Require Either Il-7 or Il-15 For Homeostatic Prolmentioning
confidence: 99%